Pelayanan Kesehatan di Puskesmas Bukit Hindu Kecamatan Jekan Raya Kota Palangka Raya - Norvia Norvitasari (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2021)
This study talked about Health Services at the Bukit Hindu Community Health Center Jekan Raya District Palangka Raya City. Because of this research how the problems that occur and what are the factors that exist in the Health Center,so that in the future what becomes a deficiency can be fulfilled and realized. The purpose of this study was to describe and analyze Health Services at Bukit Hindu Community Health Center Jekan Raya Subdistrict Palangka Raya City.The benefits of this research are theoretical benefits and practical benefits.This study uses the Fitzsimmons theory which suggests (five) public service indicators: Tangibles, Reliability, Responsiveness, Assurance and Emphaty.This research belongs to the type of descriptive research using qualitative methods. Sources of data in this study are primary data and secondary data, data collection is used by observation, interviews and documentation. In addition, the technical data collection is in the form of data reduction, data presentation and conclusion drawing.The results of this study that the facilities and infrastructure in the Bukit Hindu Community Health Center, Jekan Raya District, Palangka Raya City are still lacking, facts in the field there are still shortcomings such as lack of human resources, and there are still obstacles in the services provided.The conclusion of this study can be seen from tangible indicators that still have some shortcomings of facilities and infrastructure, reliability is quite good, responsiveness is quite responsive, guarantees are very clear in accordance with established standards, empathy there are some officers who sometimes have different attitudes and not friendly to the community. Factors supporting access to easily accessible health centers, inhibiting factors for lack of facilities and infrastructure, and slow response and even government actions.